Megan Osborne standing among collection drawers - Unidentified photographer (Colorado State University. Libraries, 2015)
Photograph of Collections Manager Megan Osborne standing among stacks of collection drawers waiting to be unpacked into the newly expanded Avenir Museum of Design and Merchandising in 2015.
Keywords: Fashion -- History; Fashion -- Exhibitions